The Rural Household Multi-Indicator Survey (RHoMIS): A rapid, cost-effective and flexible tool for farm household characterisation, targeting interventions and monitoring progress towards climate-smart agriculture - Wijk, Mark T. van; Hammond, James; Etten, Jacob van; Pagella, Tim; Ritzema, Randall S.; Teufel, Nils; Rosenstock, Todd S. (2016)
RHoMIS is a rapid, cheap, digital farm household-level survey and analytical engine for characterizing, targeting and monitoring agricultural performance. RHoMIS captures information describing farm productivity and practices, nutrition, food security, gender equity, climate and poverty. RHoMIS is action-ready, tested and adapted for diverse systems in more than 7,000 households across the global tropics. Want more info? See: http://rhomis.net/